The Influence of Interactive Visual Media in Learning Basic Volleyball Techniques on Students' Learning Interest - Kasmad, M. Rachmat; Haeril, Haeril (Sains Global Institut, Indonesia, 2025)
This study aimed to determine the effect of the use of interactive visual media on students' learning interest in basic volleyball techniques at SMA Negeri 9 Makassar. The method used was a quasi-experimental study with a pretest-posttest control group design. The sample consisted of 40 students divided into two groups: an experimental group (n=20) receiving treatment using interactive visual media, and a control group (n=20) using conventional learning methods. The descriptive analysis showed that the average learning interest score in the experimental group increased from 67.40 (SD = 6.12) in the pretest to 85.10 (SD = 5.73) in the posttest. Meanwhile, in the control group, the score increased from 66.85 (SD = 5.89) to 72.45 (SD = 6.18). The t-test results showed a significant difference between the two groups in the posttest, with a p-value of 0.000. The effect size calculation using Cohen's d yielded a value of 2.12, which is considered a large effect size. These findings indicate that the use of interactive visual media can significantly increase student interest in learning basic volleyball techniques. This media provides a more engaging learning experience, facilitates technical understanding through visualization, and encourages active student participation. Therefore, interactive visual media is recommended as an effective learning strategy in physical education at the secondary school level.